Metaphors in mathematical instruction effects on high school students' adaptability and representational thinking - Tardecilla, Patrick F.
The research investigated how Metaphorical Teaching in Mathematics influences students adaptability and representational thinking. Furthermore, it examined whether adaptability serves as a predictor of representational thinking. Using a sequential mixed-method design, it combined quantitative and qualitative approaches. The quantitative phase involved a two-group pretest-posttest quasi-experimental design with 83 Grade 9 students from a Marikina City public high school. One group was taught using metaphorical teaching, while the other received conventional instruction, both facilitated by the researcher with parallel methods. The qualitative phase included interviews, observations and output examinations to analyze students' experiences.